2016
DOI: 10.1007/s12160-016-9821-9
|View full text |Cite
|
Sign up to set email alerts
|

Enabling, Not Cultivating: Received Social Support and Self-Efficacy Explain Quality of Life After Lung Cancer Surgery

Abstract: Interventions for patients with lung cancer may focus on enhancing social support receipt within the first week after surgery, followed by a self-efficacy prompt 3 weeks later.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 34 publications
3
48
0
Order By: Relevance
“…Our findings resonate with other studies showing that lapses in self-regulation commonly occur at night in other health behaviors such as dieting (Forman et al, 2017; McKee, Ntoumanis, & Taylor, 2014) and trying to quit smoking (Fillo, Alfano, Paulus, & Baird, 2016). One implication of our findings is that, in order to maximize ecological validity, future lab-based research on sexual response and decision-making (e.g., the effects of arousal on behavior) should be conducted at times of day or in states of tiredness that more closely match the real-world conditions in which sexual decisions are commonly being made.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings resonate with other studies showing that lapses in self-regulation commonly occur at night in other health behaviors such as dieting (Forman et al, 2017; McKee, Ntoumanis, & Taylor, 2014) and trying to quit smoking (Fillo, Alfano, Paulus, & Baird, 2016). One implication of our findings is that, in order to maximize ecological validity, future lab-based research on sexual response and decision-making (e.g., the effects of arousal on behavior) should be conducted at times of day or in states of tiredness that more closely match the real-world conditions in which sexual decisions are commonly being made.…”
Section: Discussionsupporting
confidence: 92%
“…So far, much research has shown that social support and self‐efficacy are associated (e.g. Banik et al., ; Benight & Bandura, ; Duncan & McAuley, ; Ernsting, Knoll, Schneider, & Schwarzer, ; Luszczynska, Sarkar, & Knoll, ; Rackow, Scholz, & Hornung, ; Schwarzer & Knoll, ). For instance, an overview paper by Schwarzer and Knoll () re‐analysed data from a study by Schröder, Schwarzer, and Konertz () conducted with patients recovering from cardiac surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the direction of associations between self‐efficacy and support can be reciprocal, in that support received may enhance recipients’ self‐efficacy (the enabling hypothesis; Banik et al., ), whereas at the same time self‐efficacy may facilitate receipt of support (cultivation hypothesis; Hohl et al., ). A related question that has rarely been addressed so far concerns the decomposition of time‐stable and time‐varying shares of this association in couples, thereby visualising different change patterns.…”
Section: Introductionmentioning
confidence: 99%
“…For persons who find the behavior difficult, in turn, a self‐efficacy intervention may prove helpful. In Bangladesh, this might be achieved by forming women's support groups (in line with the enabling hypothesis; Banik et al., ). According to social‐cognitive theory (Bandura, ), improved self‐efficacy should strengthen motivation, and should also lead to the perception of fewer barriers, and hence finding the behavior less difficult.…”
Section: Discussionmentioning
confidence: 93%